Lipid oxidation and implications on nutrition and health of production animals - Baron, Lana Flávia; Pazinatto, Rafael; Baron, Camila Paula (Science & Technology Journals, 2020)
The oxidation process is one of the main reactions of food spoilage. Oxidation has a great influence on nutritional value and quality of products that are used in animal nutrition, especially when it comes to oils used in feed. The use of lipids is intended to enable better performance and health of the animal, providing more energy to it. The objective of this study is to approach, in general, the importance of lipids, how its oxidation occurs, the use of antioxidants and the implications of lipids for the nutrition and health of production animals. Lipids are substances that have high nutritional and energy value. However, when it comes to nutrition, the use of oxidized lipids alters the organoleptic properties of the feed, such as presence of odor, taste and change in oil viscosity, and rancidity is characteristic. Moreover, it may lead to the development of undesired physiological changes and nutritional damages, besides forming toxic substances that have great influence on disease occurrence.